The limitations of 'Black MSM' as a category: Why gender, sexuality, and desire still matter for social and biomedical HIV prevention methods. - Garcia, Jonathan; Parker, Richard G; Parker, Caroline; Wilson, Patrick A; Philbin, Morgan; Hirsch, Jennifer S (Global public health, 2016)
The USA faces disproportionate and increasing HIV incidence rates among Black men who have sex with men (BMSM). New biomedical technologies such as pre-exposure prophylaxis (PrEP) have been developed to address their HIV risk. Very little consideration, however, has been given to the diversity obscured by 'BMSM' as a category, to how this diversity relates to men's sexual partnering strategies, or to the relevance of these issues for new HIV prevention methods. We conducted a community-based ethnography from June 2013 to May 2014 documenting factors that affect the acceptance of and adherence to PrEP among BMSM. We conducted in-depth interviews with 31 BMSM and 17 community stakeholders, and participant observation. To demonstrate the diversity of social identities, we present a taxonomy of indigenous categories organised along the axes of sexual identity, sexual positioning, and gender performance. We analyse how HIV prevention strategies, such as PrEP, may be more effective if programmes consider how gender, sexuality, and sexual desire shape sexual partnering strategies. This article underlines the importance of attending to the diversity of sexual and social subjectivities among BMSM, of bringing the study of sexuality back into HIV prevention, and of integrating biomedical prevention approaches into community-based programmes.